Revolution in the shadow of the cholera epidemic. 1905 in Łódź - Sikorska, Marta (A mosaic city: The culture-oriented description, 2023)
The article outlines the most important events that took place in 1905 in Łódź. Against the backdrop of revolutionary disturbances, local doctors and social activists were preparing to fight the oncoming cholera epidemic. Poor sanitary conditions in the city and the poverty of a large part of its population caused fears that the epidemic would have a dramatic course.